IMPACT EVALUATION OF VOCATIONAL TRAINING AND EMPLOYMENT SUBSIDIES FOR THE UNEMPLOYED IN LITHUANIA - OECD (OECD, 2022)
This report on Lithuania is the tenth country study published in a series of reports looking into how policies connect people with jobs. This report is produced in the framework of a project of the OECD with the European Commission which aims to raise the quality of the data collected and their use in the evaluation of the effectiveness of active labour market policies (ALMPs).